“Evaluación de biol en la producción de papa (solanum tuberosum) variedad super chola en la asociación de mujeres productoras “Aspromoy” perteneciente a la parroquia Toacaso cantón Latacunga provincia Cotopaxi” - Simba Minta, Andrés Santiago (2024)
The study was conducted in the community of La Moya, Toacaso parish, Cotopaxi province, with the objective of evaluating organic biol at different doses and frequencies in potato (Solanum tuberosum) production. The methodology was experimental with a split-plot design (AxB) evaluating three doses (25%, 50% and 75%) and two application frequencies (8 and 15 days), with three replications plus a control. The variables to be measured were: plant height (30, 60, 90 and 120 days), number of tubers, tuber weight and yield. The results obtained indicate that T1 (dose 25% - frequency 8 days) was superior to the other treatments in the variables plant height at 120 days with 25.27 cm, tuber weight with 163.97 grams and yield with 167.3 kg/ha-1, while for the variable number of tubers the control presented a greater number of tubers with 9.63 tubers/plant, concluding that the biol did act as a fertilizer improving crop yield.